2018
DOI: 10.4103/ccd.ccd_156_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marginal adaptation of a self-adhering flowable composite resin liner: A scanning electron microscopic study

Abstract: Background:“Self-adhering composite resins,” are claimed to eliminate the need for a separate acid etching and bonding agent application step, thus simplifying the direct restorative procedure, both regarding the technique sensitivity and the duration of treatment.Aim:The aim of this study is to evaluate the marginal adaptation of self-adhering flowable composite (Dyad flow) in comparison to the conventional flowable composite (Tetric N-flow) under scanning electron microscope (SEM).Settings and Design:This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Although in vitro testing of restorative materials provides an important initial screening for their properties, the obtained results can not accurately predict the clinical performance of restorations [66]. To mimic the influence of oral environment, the restorations in the present study were subjected to thermal ageing.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro testing of restorative materials provides an important initial screening for their properties, the obtained results can not accurately predict the clinical performance of restorations [66]. To mimic the influence of oral environment, the restorations in the present study were subjected to thermal ageing.…”
Section: Discussionmentioning
confidence: 99%
“…The review showed that the main self-adhesive flowable resins evaluated were Vertise Flow (Kerr Corporation, Orange, CA, USA) [1,2,[15][16][17][18], and Fusio Dentin Liquid (Pentron Clinical, Orange, CA, USA) [19][20][21], Self-adhesive Bulk Fill Restorative (3M Oral Care, St Paul, MN, USA) [21], Filtek Supreme Ultra Flowable (3M ESPE, USA) [22], and Constic (DMG; Hamburg, Germany) [3].…”
Section: Discussionmentioning
confidence: 99%
“…This review assessed five distinct commercial brands of self-adhesive flowable composite resins (Table 2). Among the studies included, Vertise Flow resin (Kerr Corporation, Orange, CA, USA) was evaluated in six studies [1,2,[15][16][17][18], while Fusio Dentin Liquid (Pentron Clinical, Orange, CA, USA) was examined in three [19][20][21]. Additionally, one study investigated Selfadhesive Bulk Fill Restorative (3M Oral Care, St Paul, MN, USA) [22], another focused on Filtek Supreme Ultra Flowable (3M ESPE, USA) [23], and Constic (DMG; Hamburg, Germany) was analyzed in a separate study [3].…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Supplemental experiments need to be conducted in order to assess the specificities of the adhesion process and to examine the properties of the material structure. Thus, the use of scanning electron microscopy (SEM) would allow for an in-depth examination of the adhesive interface and tooth structures [24,25], whereas a semi-quantitative assessment of the chemical elements of substrates could principally be obtained using energy dispersive X-ray analysis (EDX) [26]. It is worth mentioning that EDX studies have found less application in dentistry [26][27][28], being especially associated with the fields of engineering [29] and chemistry [30].…”
Section: Introductionmentioning
confidence: 99%